Re-conceptualizing and decolonizing resilience from a peasant perspective - Santiago-Vera, T.; Rosset, P. M. [UNESP]; Saldivar, A.; Ferguson, B. G.; Méndez, V. E. (Taylor & Francis, 2021)
The objective of this initial conceptual essay is to question conventional approaches and propose a new reading–from the perspective of the peasant world–of the concept of resilience. There is a need for critical reflections on resilience that take into account the subjects of resilience, particularly in the case of peasant agriculture. We argue that to be useful in the case of peasant societies and peasant agroecology, the concept must evolve by incorporating an understanding of the peasant condition, as well as of decolonial thought and methodologies for epistemic decolonization. We emphasize that in the peasant world there is a close relationship between relative autonomy and what we call peasant resilience.
Keywords: agroecologies; chiapas; epistemology; Peasant agriculture; resilience